Naim Stifan Ateek's Palestinian Liberation Theology for The Israel-Palestine Conflict - Valentinus Fio Milinio Febriantoro; Thomas Lasmono Wibowo; JB. Heru Prakosa (Proceedings of The International Conference on Theology, Religion, Culture, and Humanities, 2024)
Palestine is a country where the population is around 4-5 million. The current Christian population in Palestine is around 6 percent of the total population. These are religiously oppressed people who are affected by the political turmoil of Israel and Palestine. This community is in dire need of a correct and adequate understanding of the theological meaning of the Palestinian experience of suffering in relation to Israel. The Bible has been misused to legitimize political interests. Naim Ateek believes that they are suffering and hopes that the Church will be able to build and explain a theology of liberation for Palestinian Christians. With the method of literature study and comprehensive reading, it is found that Naim Ateek makes a new hermeneutic so that God is not understood as a Primitive and Exclusive God as described by Israel who takes sides and discriminates, but a Universal and Inclusive God to realize justice in the spirit of compassion and peace so that it can show the harmony of God for the peace of the Palestinians and Israelis.